PENGARUH CURRENT RATIO, INVENTORY TURNOVER DAN SIZE TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Bernat Sihombing; Holfian Daulat Tambun Saribu; Goklas Fitri Kesia Samosir; Olga Nova Thia Sihombing (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to determine the significant effect of the current ratio on profitability (1), Inventory turnover on profitability (2), and size on profitability (3). In manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2015-2019. The population used in this study is consumer goods manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique was carried out by rondom. In this study, a quantitative research method was used to identify and measure more than one research variable. The sampling method in this study was purposive sampling. The method used for data analysis used descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing either simultaneously or partially. The results obtained from this study are as follows (1) current ratio is not significant to profitability (2) inventory turnover has a positive and significant effect on profitability, (3) size is not significant and has no effect on profitability. Simultaneously, all variables (Current ratio, Inventory turnover, and Size) have a positive and significant effect on the profitability of manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange for the 2015-2019 period.